Association of Body Mass Index (BMI) and Body Fat Percentage in Sports Science Students - Janah, Ulfatun; Indah Kartika Zebua, Dwi; Gulo, Florentina; Noferlin Gulo, Intan; Amin, Nur (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Body Mass Index (BMI) is widely used as a simple indicator of nutritional status, but it has limitations because it cannot differentiate between muscle mass and fat mass. This limitation often leads to misclassification, particularly among athletes or physically active individuals. To provide a more accurate depiction of body composition, body fat percentage measurements are required. This study aimed to examine the relationship between BMI and body fat percentage among Sports Science students at Ngudi Waluyo University in 2026, thereby evaluating the effectiveness of BMI as an indicator of nutritional status in this population. A quantitative observational design with a cross-sectional approach was employed, involving 46 students (39 males and 7 females). BMI was calculated from body weight and height, while body fat percentage was determined using skinfold thickness measurements at seven anatomical sites based on the Jackson & Pollock method, with conversion to body fat percentage using Siri’s equation. Data were analyzed using Pearson’s correlation test to assess the strength and significance of the relationship between BMI and body fat percentage. The results revealed variations in BMI categories ranging from underweight, normal, to overweight. Students with higher BMI generally exhibited greater body fat percentages, while those with normal or underweight BMI showed moderate to low body fat percentages. For example, Ulva Lutviyah (BMI 29.6) had a body fat percentage of 21.9%, whereas Indah Karunia Telaumbanua (BMI 20.4) had 12.6%, and Romanus Ficerman Gulo (BMI 18.8) had approximately 7%. Pearson’s correlation analysis yielded r = 0.82 with p < 0.05, indicating a strong and statistically significant positive relationship between BMI and body fat percentage. However, certain cases highlighted BMI’s limitations, such as overweight students with relatively low body fat due to higher muscle mass. In conclusion, BMI can serve as an initial indicator of nutritional status, but it should be complemented with body fat percentage measurements to provide a more accurate evaluation. These findings emphasize the importance of combining BMI and skinfold assessments in monitoring student health and fitness, while future studies should consider larger samples and additional variables such as dietary patterns, physical activity, and muscle mass.